2013
DOI: 10.1016/j.joca.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional turbo spin-echo magnetic resonance imaging (MRI) and semiquantitative assessment of knee osteoarthritis: comparison with two-dimensional routine MRI

Abstract: Semiquantitative assessment of knee OA can be reliably performed using 3D TSE MRI, showing substantial to almost perfect agreement and high accuracy when compared to routine 2D TSE MRI. 3D TSE MRI also takes less time, which is important for large OA studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
(20 reference statements)
1
25
0
Order By: Relevance
“…Their investigation showed that image quality of 2D sequence in comparison with 3D isotropic sequences in evaluating cartilages and TFCC is better in 2D sequences. In a study carried out by Crema et al (9) in 2013 on osteoarthritis knee joint showed that SNR of 3D FSE (SPACE) in comparison with 2D FSE is higher and thus more reliable for diagnosis and determining the extension of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Their investigation showed that image quality of 2D sequence in comparison with 3D isotropic sequences in evaluating cartilages and TFCC is better in 2D sequences. In a study carried out by Crema et al (9) in 2013 on osteoarthritis knee joint showed that SNR of 3D FSE (SPACE) in comparison with 2D FSE is higher and thus more reliable for diagnosis and determining the extension of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability of the ACLOAS using dedicated extremity systems and 3 T scanners remains to be shown but should be expected in agreement with the experience with other OA scoring tools and assessment of traumatic knee injury 37,38 . Further, recently introduced 3D fast spin echo sequences could probably also be used for ACLOAS assessment as initial experience with these sequences in OA assessment showed comparable results to scoring of standard 2D sequences 39,40 .…”
Section: Locationmentioning
confidence: 99%
“…Subchondral traumatic and degenerative BMLs are assessed using fat suppressed water sensitive sequences such as STIR, proton density or T2 weighted sequences. These may be two-or three dimensional in regard to acquisition 39,40 . Cartilage, osteochondral injury and BMLs are scored in 14 articular subregions, while osteophytes are assessed at eight defined locations or sites.…”
Section: Appendixmentioning
confidence: 99%
“…20 Moderately T2-weighted 3D TSE was found useful, reliable, and time efficient for assessing the whole-organ magnetic resonance imaging score (WORMS) in osteoarthritis studies. 21 A volunteer study at 3 T, dedicated to small cartilage detail, 22 reported an intermediate ranking of 3D TSE compared with 3D double-echo steady state and 3D fast low-angle shot with respect to cartilage-fluid CNR. The moderately T2weighted 3D TSE sequence was superior to 3D true-fast imaging with steady-state precession in assessing the repair status of cartilage using the magnetic resonance observation of cartilage repair tissue (MOCART) score and showed fewer artifacts in the subjective rating in 37 patients after matrix associated chondrocyte implantation.…”
Section: Knee (►Fig 4)mentioning
confidence: 99%